The Effectiveness of the Discussion Debate Learning Model in Pancasila Education to Train Critical Thinking in Grade XII Students at SMAN 1 Karanganyar: Efektivitas Model Pembelajaran Diskusi Debat dalam Pendidikan Pancasila untuk Melatih Berpikir Kritis pada Siswa Kelas XII di SMAN 1 Karanganyar - Widyastuti, Winda; Noventari, Widya (Civic Education Perspective Journal, 2026)
This study aims to describe the implementation, impact, and challenges of implementing the discussion debate learning model in improving the critical thinking skills of grade XII students in the Pancasila Education subject at SMAN 1 Karanganyar. This study uses the Classroom Action Research (CAR) method with two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques include observation, interviews, documentation, and critical thinking ability tests, with data analysis carried out qualitatively and quantitatively descriptively. The results of the study indicate that the discussion debate model is able to improve students' critical thinking skills in the aspects of expressing opinions, contributing to learning, activeness, and information processing. The novelty of this study lies in the application of the discussion debate model that has never been used before in the school, as well as the active use of the CAR approach by the researcher. The implications of this study indicate that the discussion debate model can be an effective and contextual alternative learning strategy in civic education, because it encourages active participation, argumentative dialogue, and a critical understanding of Pancasila values. This finding provides an important contribution to the development of science in the field of citizenship education, particularly in forming students who not only understand the concept of citizenship theoretically, but are also able to think critically, communicatively, and reflectively as active and responsible citizens.